Design for CNC : furniture projects and fabrication technique - Filson, Anne, ....-; Rohrbacher, Gary; Kaziunas France, Anna, ....- (San Francisco : Maker Media, 2017)
Design, DIY, and computer-controlled fabrication are a powerful combination for making high-quality customized things. Written by the founders of the architecture, design, and research firm Filson and Rohrbacher, this book takes you through the basics of CNC fabrication, the design process, production, and construction of your own furniture designs. Through their AtFAB series of projects, accompanied by an overview of digital techniques and design thinking, this book introduces the knowledge and skills that you'll find widely applicable across all kinds of CNC projects. Not only will you learn how to design, fabricate, and assemble a wide range of projects, you'll have some great furniture to show for it! While 3D printing has been grabbing headlines, high school, college, library, and other public makerspaces have been making things with CNC machines. With a CNC router, you can cut parts from strong, tactile, durable materials like wood. Once you have your design and material, you can set up your job and let it run. When it's done, you can put the project together for an heirloom of your own. While 3D printing can make exciting things with complex designs, CNCs are the digital workhorses that produce large-scale, long-lasting objects.